Working memory capacity in Generalized Social Phobia - Amir, Nader (2011)
Research suggests that understanding complex social cues depends on the availability of cognitive resources (e.g., Phillips, Channon, Tunstall, Hedenstrom, & Lyons, 2008). In spite of evidence suggesting that executive control functioning may impact anxiety (e.g., Eysenck, Derakshan, Santos, & Calvo, 2007), relatively few studies have examined working memory in individuals with Generalized Social Phobia (GSP). Moreover, few studies have examined the role of threat-relevant content in working memory performance in clinically anxious populations. To this end, the present study assessed working memory capacity (WMC) in individuals with Generalized Social Phobia and non-anxious controls using an Operation Span task using threat relevant and neutral stimuli. Results revealed that non-anxious individuals demonstrated better WMC than individuals with GSP for neutral words, but not for social threat words. Individuals with GSP demonstrated better WMC performance for threat words relative to neutral words. These results suggest that individuals with GSP may have relatively enhanced working memory performance for salient, socially-relevant information. This enhanced working memory capacity for threat relevant information may be the result of practice with this information in GSP.